Relevansi Sirah Nabawiyah dalam Konteks Modern: Penelitian - Riyadhotul Ilmi; Lidia Artika; Marzuki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article explores the relevance of Sirah Nabawiyah, the life story of Prophet Muhammad (peace be upon him), in the context of modern life, especially in terms of leadership and Islamic preaching (da’wah). In today's era of globalization, humanity faces various challenges such as moral decline, loss of compassion, and weak leadership character. In this situation, the prophetic values found in Sirah Nabawiyah—such as honesty, justice, patience, compassion, and responsibility—are essential to be used as inspiration and life guidance. This research uses a descriptive qualitative method with a library research approach, collecting data from historical sources, Islamic literature, and other academic references. The findings show that Sirah Nabawiyah has strong relevance in shaping personal character, building just and wise leadership, and promoting a humanistic and thoughtful form of da’wah in today’s life. Therefore, it is highly recommended for the young generation, especially students, to study and apply these prophetic values in daily life.